Using Word wall Media to Increase Students’ English Vocabulary Treasury - Ervin, Ervin; Ariyani, Amra; Mawe, Rusdin (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. Some problems in the students’ vocabulary mastery are quite diverse, start from spelling error, pronunciation, and the right word choice in wiring even in speaking. This research aimed to analyze the enhancement of students’ English vocabulary related to pronoun; subjective, objective, and possessive adjective of the students of class XII MIPA 1. By the using of word wall media, this research was classroom action research. The subjects of this research were taken from the students of XII MIPA 1 at SMA Negeri 2 wangi-wangi which consist of 16 female and 15 male students. The techniq of data collection used test and non-test. Next, the result of this research showed that the score average of English vocabulary test in the first cycle was 39,00, while the second cycle was 56,6. The second cycle experienced improvement as much as 17,6. Therefore, the students’ outcomes in the vocabulary mastery by the use of word wall Media were increased. The implication of this research is that the English teacher to utilize word wall learning media since it could increase students' English vocabulary mastery. Keywords: Vocabulary, Media, Word wall